"We saw human guinea pigs explode". Issue 7593 (15th March 2007) - Stobbart, L; Murtagh, M J; Rapley, T; Ford, G A; Louw, S J; Rodgers, H
Abstract : L Stobbart and colleagues examine newspaper coverage of adverse events in the TGN1412 trial